ABOUT THE MORPHOLOGY OF BUD SCALES AND CATAPHYLLS OF ULMUS GLABRA HUDS. (ULMACEAE) - I. S. Antonova; A. S. Popova (Труды по прикладной ботанике, генетике и селекции)
Background. Specific features of plant development and mechanisms ensuring such processes are expressly linked with the  structure of buds and hence the leaf series formed on lateral shoots.Materials and methods. The material of the study was the shoots  of the second to fifth orders of nineteen plant samples in their  generative age (G1, G2) grown in the well-lighted habitats in the  Park of Petrozavodsk and the Park of Komarovo Town (St.  Petersburg). All buds on vegetative and vegetative-generative shoots (more than 250) were investigated. The leaf organs of the formed  seventy-nine vegetative buds of Ulmus glabra Huds. were  consistently disassembled and measured under an MBS-9 binocular.  The analysis of the development of bud scales in unfolding buds made it possible to observe structural features unavailable in a  static study of buds. Results and conclusions. The growth of the leaf organs in a series was found to occur in different ways. Almost completely suberized  external scales represented a thickly grown leaf base fused with  poorly developed stipules. The scales from the first to the fourth did  not grow at all when the bud was unfolding. The fifth and the sixth  scales showed weak intercalary growth during the unfolding. The tips  of the seventh up to the tenth scales were weakly suberized and had two blades which formed a cap covering the tip of  the bud. The scale which preceded the emergence of a leaf sprout with a leaf blade had on its tip pronounced lobes and a depression  between them with a rounded bottom and hairs along the edge. It  was followed by a sprout with large separated stipules, an almost  unpronounced leaf base and a differentiated leaf blade; hence, there is a threshold in the differentiation of leaf sprouts. In the axil  of each growing scale, a small dormant bud was set. Thus, the  number of leaf organs on a shoot after unfolding was 10-15, while  the leaves of the middle formation did not exceed 3-5, and besides  only one growth period was observed in a majority of U. glabra  plants in their generative age state. Using U. glabra as an example, the performance of the threshold mechanism within the  genetic program of vegetative shoot development was demonstrated.